Referral proformas improve compliance to national colorectal 2-week wait targets: does this affect cancer detection rates? - Jani, A; Jenner, L; Ma, F; Dutton, S; Stevens, R; Sharma, R (2012)
AIM: To facilitate implementation of National Institute for Health and Clinical Excellence (NICE) guidelines for urgent colorectal cancer referral, local cancer networks have promoted the use of standardized proformas in primary care. This clinical audit assessed use of the proforma within the Thames Valley Cancer Network (TVCN) to see whether increased proforma use was associated with higher compliance to NICE guidelines and higher cancer detection rates. METHOD: All 2-week wait referrals for lower bowel cancer to the six Acute NHS Trusts in the TVCN received during the month of June 2010 were identified, anonymized and analysed in relation to colorectal cancer detection rates. RESULTS: Of the 586 referrals audited, proforma usage varied significantly across the six Acute NHS Trusts from 18% to 96%. Referral letters from primary care had NICE compliance ranging from 30 to 50%. In those which received a referral protocol, 50-90% were NICE compliant. Proforma use was associated with higher cancer detection rates (P = 0.03). CONCLUSION: These results have wide-ranging implications since they suggest that the adoption of a simple proforma in primary care can improve the effectiveness of referral for suspected cancer.